Foot and Ankle Ability Measure: cross-cultural translation and validation of the Italian version of the ADL module (FAAM-I/ADL) - Sartorio, Francesco; Vercelli, Stefano; Bravini, Elisabetta; Bargeri, Serena; Moroso, Michela; Plebani, Giuseppe; Ferriero, Giorgio (La Medicina del Lavoro, 2014)
Background: Valid and reliable outcome measures are fundamental for evaluating and comparing the effects of rehabilitation. Among the different tools used for the assessment of musculoskeletal disorders of the lower limb, the Foot and Ankle Ability Measure (FAAM) has been shown to have good psychometric properties. However, it has not yet been translated into Italian. The module regarding the performance of daily living activities (FAAM/ADL), in particular, can be applied also in an occupational setting. Objective: To obtain an Italian version of the FAAM, and to validate the FAAM-I/ADL. Methods: The cultural adaptation was performed according to international guidelines for forward/backward translation. The activities of daily living (ADL) module of the FAAM-I (FAAM-I/ADL) was validated with classical test theory methods in a convenience sample of 57 patients. Different parameters were calculated: internal consistency (Cronbach’s α and item-to-total correlation); criterion validity, through Pearson’s correlation (r) with the Lower Extremity Functional Scale (LEFS); test-retest reliability (ICC2,1); Standard Error of Measurement (SEM); and Minimal Detectable Change (MDC95). Results: The statistical analysis showed good internal consistency (Cronbach’s α=.96, item-to-total correlation ranged between .51 and .85), high criterion validity (r=.66, p